Design of a guide for tree planting on the avenues of the Eastern Macrosector of Barquisimeto, Lara State (Gaceta Técnica, 2026)
This study addresses the challenges of urban tree planting in the eastern macro-sector of Barquisimeto, Venezuela. Using a descriptive and field-based approach, it diagnoses the damage and failures caused to pedestrian infrastructure and road medians by tree species. The research reveals that the lack of technical criteria in the selection of species, such as Neem (Azadirachta indica) and Pilón (Andira inermis), along with their inappropriate placement, has generated significant problems in the urban environment. Therefore, the ultimate goal of the study is to develop a practical guide that facilitates the proper management of urban trees, recognizing the multiple benefits they can offer. To achieve this, a diagnosis of existing damage and the identification of species best suited to local conditions are proposed. The results obtained underscore the urgent need for intervention to correct current practices and ensure both the health and functionality of urban trees. The proposed guide is conceived as an essential tool for local authorities and urban planners, thus contributing to the creation of a more resilient urban environment
Keywords: urban tree planting; Barquisimeto Eastern Macrosector; damage to road infrastructure